Digital Dermatoscopy Method for Human Skin Roughness Analysis - Suprijanto Suprijanto; V. Nadhira; Dyah A. Lestari; E. Juliastuti; Sasanti T. Darijanto (LPPM ITB, 2011)
In this study we propose a digital dermatoscopy method to measure the human skin roughness. By using this method we eliminate the use of silicon replica. Digital dermatoscopy consists of handheld digital microscope, image processing and information extraction of skin roughness level. To reduce the noise due to the variation of reflection factor on the skin we use median filter. Hence, by Fourier transform the skin texture is imaged in terms of 2D frequencyspatial distribution. Skin roughness is determined from its entropy, where the roughness level is proportional to the entropy. Three types of experiment have been performed by evaluating: (i) the skin replicas; (ii) young and elderly skin; and (iii) seven volunteers treated by anti wrinkle cosmetic in three weeks period. We find that for the first and second experiment that our system did manage to quantify the roughness, while on the third experiment, six of seven volunteers, the roughness are succeeded to identify.